2017
DOI: 10.1126/science.aal5240
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fusobacterium persistence and antibiotic response in colorectal cancer

Abstract: Colorectal cancers comprise a complex mixture of malignant cells, non-transformed cells, and microorganisms. Fusobacterium nucleatum is among the most prevalent bacterial species in colorectal cancer tissues. Here we show that colonization of human colorectal cancers with Fusobacterium and its associated microbiome, —including Bacteroides, Selenomonas, and Prevotella species, —is maintained in distal metastases, demonstrating microbiome stability between paired primary and -metastatic tumors. In situ hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
882
3
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,067 publications
(981 citation statements)
references
References 43 publications
29
882
3
8
Order By: Relevance
“…Increased loads of Fn are associated with advanced CRC stages (6,1618) and with poor prognoses (19,4346). Mima et al showed that colon cancer-specific death, but not overall survival is associated with high levels of tissue Fn (43).…”
Section: Characteristics Of Fusobacterium-associated Crcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased loads of Fn are associated with advanced CRC stages (6,1618) and with poor prognoses (19,4346). Mima et al showed that colon cancer-specific death, but not overall survival is associated with high levels of tissue Fn (43).…”
Section: Characteristics Of Fusobacterium-associated Crcsmentioning
confidence: 99%
“…They also demonstrated that antibiotic treatment not only reduced the Fusobacterium load but also inhibited growth of xenograft tumors from patients, suggesting that infection by Fusobacterium accelerates tumor growth in vivo. (46). …”
Section: Characteristics Of Fusobacterium-associated Crcsmentioning
confidence: 99%
“…Recently, high-profile studies have demonstrated the role of the microbiome in regulating diverse processes, such as the efficacy of PD-1 treatments for carcinoma/melanoma, the promotion of metastasis in colon cancer, and whole body composition via the circadian clock (Wang et al 2017b;Gopalakrishnan et al 2017;Routy et al 2017;Bullman et al 2017). The exciting potential of understanding the microbiome for translational research was outlined by Miko et al, in CBT (Miko et al 2016).…”
Section: Clinical Influences Of the Microbiomementioning
confidence: 99%
“…Accumulating evidence indicates that the gut bacteria play a crucial role in human health (1), and the dysbiosis of the gut microbiota is associated with various disorders, including obesity, diabetes, inflammatory bowel disease, and many types of cancer especially colorectal cancer. According to emerging studies, several bacterial species [Fusobacterium nucleatum ( F. nucleatum ), Bacteroides fragilis , and Escherichia coli ] appeared to have a critical role in the colorectal carcinogenesis (2,3). In the tumor microenvironment of colorectal carcinoma, there should be a complicated community of cancer cells, immune cells, and a great number of microorganisms.…”
mentioning
confidence: 99%
“…The fraction of colorectal cancer with F. nucleatum increases linearly along the large intestinal subsites from the rectum to the cecum, based on a continuum model of pathogenic influences of gut bacteria on colorectal carcinogenesis (9). An experimental study suggests that metastasis of F. nucleatum -present colorectal cancer might be prohibited by antimicrobial interventions (3). Human population-based studies indicate that an enrichment of F. nucleatum is associated with high-level microsatellite instability (MSI), advanced disease stage, low-level T-cell infiltration in colorectal carcinoma tissue (7), and worse clinical outcome (8).…”
mentioning
confidence: 99%